Communication of Corporate Social Responsibility and Loyalty of Customer’s In Kuala Lumpur Hypermarket Industry - Kadhim, Kadhim Ghaffar; Harun, Amran; Hamawandy, Nawzad Majeed; Qader, Khowanas Saeed; jaf, Rizgar Abdullah Sabir; Jamil, Diyar Abdulmajeed; Rashid, Jwan Sadallah (The journal of contemporary issues in business and government, 2021)
Purpose of the study This study aims at contributing to assessing the impact of corporate social responsibility communications on the loyalty of customers in the Hypermarket Industry in Kuala Lumpur. It focuses on deterioration and the lack of quality service in the hypermarket.Design/methodology/approach The hypotheses of the study are to recognize the relationships between variables CSR communications (corporate website, public relations, advertising, social media) and customer loyalty. Each of them was tested for study scope by regression equation using the SPSS and Smart PLS software. This study enhances its empirical validity by collecting data from 384 respondents in Kuala Lumpur of Malaysia. Findings Results of the statistical analysis show that acceptance of central research hypothesis the existence of a positive relationship between variables CSR communications (corporate website, public relation, advertising, social media) and customer loyalty and this means the corporate social responsibility communications in the applied hypermarket are to understand the importance of quality services. Quality services from the hypermarket contribute to making the organization's effectiveness more positive to achieve organizational goals and improve overall performance. This results in increased customer loyalty, which requires a joint action starting from the hypermarket management to the simplest employee. Social implications The research has been concluded with several recommendations. The most important one is that hypermarkets must-have experiences, knowledge, and outstanding abilities to work together for the best performance by the impact on customers to make them more loyal to the hypermarket. Originality/value This paper establishes the role of variables CSR communications and customer loyalty for the hypermarket industry in Malaysia. Additionally, the empirical results focus on analyzing CSR's impact on customer behavior and strongly encourage hypermarkets to continue investing; CSR communication (corporate website, public relations, advertising, social media) can be strategic marketing tools to promote customer loyalty of hypermarket.